Photobiomodulation therapy’s impact on angiogenesis and osteogenesis in orthodontic tooth movement: in vitro and in vivo study - Jietong Zhong; Xinyu Zhang; Yaru Ruan; Yue Huang (BMC Oral Health, 2024)
Abstract Background This study explores the effectiveness of Photobiomodulation Therapy (PBMT) in enhancing orthodontic tooth movement (OTM), osteogenesis, and angiogenesis through a comprehensive series of in vitro and in vivo investigations. The in vitro experiments involved co-culturing MC3T3-E1 and HUVEC cells to assess PBMT’s impact on cell proliferation, osteogenesis, angiogenesis, and associated gene expression. Simultaneously, an in vivo experiment utilized an OTM rat model subjected to laser irradiation at specific energy densities. Methods In vitro experiments involved co-culturing MC3T3-E1 and HUVEC cells treated with PBMT, enabling a comprehensive assessment of cell proliferation, osteogenesis, angiogenesis, and gene expression. In vivo, an OTM rat model was subjected to laser irradiation at specified energy densities. Statistical analyses were performed to evaluate the significance of observed differences. Results The results revealed a significant increase in blood vessel formation and new bone generation within the PBMT-treated group compared to the control group. In vitro, PBMT demonstrated positive effects on cell proliferation, osteogenesis, angiogenesis, and gene expression in the co-culture model. In vivo, laser irradiation at specific energy densities significantly enhanced OTM, angiogenesis, and osteogenesis. Conclusions This study highlights the substantial potential of PBMT in improving post-orthodontic bone quality. The observed enhancements in angiogenesis and osteogenesis suggest a pivotal role for PBMT in optimizing treatment outcomes in orthodontic practices. The findings position PBMT as a promising therapeutic intervention that could be seamlessly integrated into orthodontic protocols, offering a novel dimension to enhance overall treatment efficacy. Beyond the laboratory, these results suggest practical significance for PBMT in clinical scenarios, emphasizing its potential to contribute to the advancement of orthodontic treatments. Further exploration of PBMT in orthodontic practices is warranted to unlock its full therapeutic potential.